How 'Pastoral' is Pastoralism? Dietary Diversity in Bronze Age Communities in the Central Kazakhstan Steppes. (22nd August 2014) - Lightfoot, E.; Motuzaite‐Matuzeviciute, G.; O'Connell, T. C.; Kukushkin, I. A.; Loman, V.; Varfolomeev, V.; Liu, X.; Jones, M. K.
Abstract : Steppe communities have traditionally been viewed as pastoralist groups with similar herd‐based economies. Recent scholarship, however, warns against assumptions of homogeneity and new scientific techniques are providing a more nuanced approach to steppe archaeology, with increasing indications of diversity. This recent evidence further suggests that considering these communities as primarily pastoralist may hide a variety of subsistence strategies, such as fishing and cultivation. Here, we consider direct evidence for diet (in the form of stable isotope analysis) from Bronze Age communities from central Kazakhstan, in the semi‐arid steppe zone. We find that the diversity recently suggested for communities across the steppe zone can be found within sites in the Karaganda region. This suggests that individuals exercised choice in their dietary habits that led to dietary differences large enough to be detectable isotopically. The results also highlight the inclusion of fish in the diet of these 'pastoral' populations, with indications that some individuals in the Final Bronze Age consumed notable amounts of millet. This shows that these 'pastoralist' economies also engaged in fishing throughout the Bronze Age, with millet cultivation becoming increasingly important in the Final Bronze Age. As such, our understanding of what it means, in this context, to be a pastoralist requires further consideration.